Assessing of executive functions in daily life in preterm children aged 3–4 years old from the “Behavior Rating Inventory of Executive Function—Preschool version” questionnaire - Reynold de Seresin, Magali; Roy, Arnaud; Theveniaut, Camille; Le Goff, Justine; Chopin, Coline; Rouger, Valérie; Roze, Jean-Christophe; Flamant, Cyril; Muller, Jean-Baptiste (Frontiers in Pediatrics, 2023)
Background Executive functions (EFs) are a set of neuropsychological skills permitting solving problems in a new situation by regulating action, behavior, and emotional response. As cerebral maturation remains vulnerable in preterm children, a higher risk of developing cognitive disorders including EFs exist compared to term children. Aims The aim of this study was to estimate the incidence of preschool EF impairments through proxy reports in children born preterm before 34 weeks of gestational age using the Behavior Rating Inventory of Executive Function—Preschool (BRIEF-P) version. Secondary aims were to report neonatal, child, or socioeconomic factors associated with EF disorders. Results Parents of 357 children born preterm aged 3–4 years old completed the BRIEF-P version. Impairment in EFs was clinically significant for 13.5% of preterm children (n = 47; 95% CI = 0.10–0.18) compared to 5.1% in term children. A low parental socioeconomic level was significantly associated with impaired parent-rated EF (19.1% vs. 5.3%, p = 0.003). Conclusions Proxy reports of EF impairment are about twice as frequent as in term children. EF difficulties are not related to neonatal or child severity factors in contrast with the parental socioeconomic level. Using a parent-rated questionnaire may be a useful and easy tool to identify early the daily life impact of EF disorders on clinical follow-up of preterm children. This study was recorded in the Clinical Trials Register under identifier NCT03700463.